2011
DOI: 10.1093/bja/aer269
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of the coronary endothelial glycocalyx: effects of hypoxia/reoxygenation vs ischaemia/reperfusion

Abstract: Both ischaemic and hypoxic hypoxia initiate glycocalyx degradation, promoting an increase in permeability. A contributing mechanism could be purine-mediated degranulation of resident mast cells, with liberated tryptase β acting as potential 'sheddase'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 35 publications
1
63
0
3
Order By: Relevance
“…1 In the present study, we confirmed that ischemia-reperfusion injury can cause degradation of endothelial glycocalyx in liver tissues. 2,8,10,27,28 Pretreatment with sevoflurane significantly reduced the shedding of HS and Syn-1 after the ischemia-reperfusion injury. 12,13 Similarly, the ischemia-reperfusion injury can cause the destruction of the endothelial glycocalyx in the heart tissues of guinea pigs and humans.…”
Section: Discussionmentioning
confidence: 97%
“…1 In the present study, we confirmed that ischemia-reperfusion injury can cause degradation of endothelial glycocalyx in liver tissues. 2,8,10,27,28 Pretreatment with sevoflurane significantly reduced the shedding of HS and Syn-1 after the ischemia-reperfusion injury. 12,13 Similarly, the ischemia-reperfusion injury can cause the destruction of the endothelial glycocalyx in the heart tissues of guinea pigs and humans.…”
Section: Discussionmentioning
confidence: 97%
“…These studies disclose only one part of the problemddegradation of heparan sulfate moieties, which, however, were shown to be dispensable for the maintenance of the barrier properties of glycocalyx. 18 Annecke et al 19 proposed that the loss of glycocalyx is initiated by the purine metabolite-induced degranulation of resident mast cells and release of tryptase b acting as a sheddase. The instantaneous dilution of tryptase b in the bloodstream should, however, reduce the impact of this factor on ESG.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cytoskeletal derangement and hypercontracture induce gap formation, [68][69][70][71] which is enhanced by extracellular adenosine but attenuated by extracellular ATP. 72 Degradation of the glycocalyx also contributes to reduced endothelial barrier function and edema formation 66,73,74 ; tumor necrosis factor α is an important mediator of glycocalyx degradation, 75 and glycocalyx degradation also promotes leukocyte 76 and platelet adherence. 77 Exogenous nitric oxide preserves vascular integrity and attenuates edema formation through protection of the glycocalyx.…”
Section: Vascular Permeability: Edemamentioning
confidence: 99%